Experimental determination of trough bridges pressure distribution - Sarmiento, Silvia; González-Libreros, Jaime; Sas, Gabriel; Enoksson, Ola; Höjsten, Tommy (Luleå tekniska universitet, Byggkonstruktion och brand, 2024)
The IronOre line between Narvik in Norway and Luleå in Sweden faces challenges with aging bridges and an increase in allowable axle loads. In this line, reinforced concrete trough bridges constitute about 50% of the bridge population; therefore, they are crucial for the country’s economy. An essential factor of trough bridge design is how traffic loads are distributed on the concrete surface. Thus, in this study, a laboratory campaign was implemented by monitoring the pressure on the slab and beams of a new full-scale trough bridge. The monitoring was made using load cells placed on the slab and beam surfaces at points of interest. The pressure was measured for different axle load levels and static and cycling loads. This study belongs to a more extensive experimental campaign where further tests on load distribution are planned. The results show how the loads are distributed among the sleepers and the final transversal and longitudinal distribution shapes on the bridge. Funder: Industry program for research and innovation of Construction for the Transport sector (BBT); Full text license: CC BY-NC-ND; ISBN for host publication: 978-1-032-77040-6, 978-1-032-77560-9, 978-1-003-48375-5